Comparative study on the healing potential of Persea americana Mill. (avocado) and Syzygium samarangense (blume) Merr and Perry. (makopa) crude fruit extract on induced burns on Mus musculus Linn. (albino mice). - Estiva, Aivette Ashley B. (2016)
ABSTRACT see Upload (BIO 1527 2016)